Uticaj nivoa transferina na akumulaciju gvožđa kod pacijenata sa beta-talasemijom zavisnom od transfuzije: Analiza specifična za genotip: Transferrin Impact on Iron Overload in TDT - Liang, Yidan; Zhang, Xinhua; Huang, Binbin; Huang, Yushan; Liao, Liuhua; Huang, Yueyan; Huang, Ken; Lao, Jinquan; Feng, Xiaoqin; Lin, Bin; Long, Xingjiang; Liu, Zhixiang; et al. (Journal of Medical Biochemistry, 2025)
Background: Serum ferritin (SF) is used to monitor secondary iron overload in beta-thalassemia (β-thalassemia). Transferrin (TRF) has been shown to reverse iron accumulation in experimental models, but its role in transfusion-dependent beta-thalassemia (TDT) patients remains unclear. This study aims to explore the relationship between TRF and SF in TDT patients and to reveal the unique connection between specific genotypes and iron metabolism, providing potential therapeutic targets for clinical practice.Methods: This cross-sectional study includes 817 TDT patients (β0/β0 genotype: n=560; β0/β+ genotype: n=257). We use genotype-phenotype analysis and employ logistic regression and restricted cubic spline (RCS) curves to assess the association between TRF and SF.Results: Significant differences were observed between the β0/β0 and β0/β+ genotypes in terms of age at first transfusion, transfusion requirements, chelation initiation age, reticulocyte count, red blood cell count, red cell distribution width-coefficient of variation (RDW-CV), fetal hemoglobin (HbF) level, splenomegaly, and SF. β0/β0 patients presented with more severe clinical phenotypes. SF was significantly associated with TRF, HbF, RDW-CV, and chelation therapy. RCS analysis revealed a dose-response relationship with a negative linear correlation between TRF and SF (OR=0.26, P